2D: 4D, lateralization and strength in handball players - Eler, N.; Eler, S. (Journal of Education and Training Studies, 2018)
Lateralization, which is also known as hand preference, and 2D:4D finger ratio is a sign of prenatal testosterone and known to be associated with strength. The aim of this study is to investigate the relationship between 2D: 4D, lateralization and hand grip strength in relation to hand and forearm that are thought to be effective in handball in elite handball players. 67 female and 67 male elite players participated in this study. The height, weight, body-mass index and hand preference of these athletes have been identified and 2D: 4D finger measurements and hand grip strength tests were performed. When identifying the preferences regarding lateralization, the hand distribution preference was determined by the Oldfield questionnaire and evaluated using the Geschwind score. After photocopy images of the two hands of the athletes were taken, their finger lengths were measured Hand grip strength was determined by a Jamar hydraulic dynamometer. Strong correlation was found especially between 2D: 4D and dominant hand grip strength in male and female elite handball players. The ratio of left-handedness due to the positions of players during the game among male and female athletes has been found to be higher than that of the general population. With regard to gender, 2D: 4D was found to be lower in males than females but hand grip was found to be higher in males than females. Besides, a significant correlation between height and BMI with 2D:4D, sport age, height, body weight and hand grip strength was found. This study emphasizes the importance of 2D: 4D, handgrip strength and hand preference in handball.